Accelerating organization : embracing the human face of change - Maira, Arun (McGraw-Hill New YorkUS, 1997)
Examines the 6 principal components of a successful organizational change process and suggests practical ways of managing them. Uses the acronym, SCHOOL, and identifies the components as follows: strategic flexibility, change-readiness, hidden leverage,, operational alignment, organizational involvement, and, learning acceleration.